Does measurement of the jugular foramen diameter on MRI help to differentiate transverse sinus thrombosis from unilateral transverse sinus hypoplasia? - MİDİ, İPEK (SPRINGER-VERLAG ITALIA SRL, 2021)
Background and Purpose The transverse sinus (TS) is a frequent location of cerebral venous thrombosis. However, unilateral TS hypoplasia is a frequent variation and radiological imaging pitfall in the diagnosis because it may mimic unilateral TS thrombosis. The purpose of this study is to find a cutoff value for bilateral jugular foramen (JF) diameter ratios on magnetic resonance imaging (MRI) for differentiating TS thrombosis from TS hypoplasia. Materials and Methods We retrospectively reviewed magnetic resonance venography results for 174 patients with reduced unilateral TS caliber resulting from either unilateral thrombosis (80 patients) or unilateral hypoplasia (94 patients). We calculated the ratio by proportioning the diameter of the JF ipsilateral to the TS with caliber reduction to the diameter of the contralateral JF. The Mann-WhitneyUtest was used to compare the ratios between thrombosis and hypoplasia groups, and the cutoff value was calculated by receiver-operating characteristic curve analysis. Results The ratio of bilateral JF diameters was lower in patients with hypoplasia than those with thrombosis (P < .01). The cutoff value to determine the diagnosis of TS hypoplasia with maximum accuracy was 0.638, with a sensitivity of 91.3% and specificity of 64.9%. Conclusion In equivocal cases, calculating the cutoff value by proportioning the diameter of JF ipsilateral to the TS with caliber reduction to the contralateral JF seems to be an efficient, quick, and straightforward method and valuable aid to differentiate TS thrombosis from TS hypoplasia.
Keywords: Cerebral venous thrombosis; Transverse sinus; Transverse sinus hypoplasia; MR venography; MRI; CEREBRAL VENOUS THROMBOSIS; VENOGRAPHY; DIAGNOSIS